(untitled) (Academicia Globe: Inderscience Research, 2023)
The problem of renewable raw materials for the production of biologically active preparations used in the national economy and medicine is one of the most important tasks of chemical technology. Based on the results of our research, it has been established that a number of valuable products such as chlorophyll, porphyrins and their metal complexes, intermediates for the synthesis of vitamins E, K, carotene, biflovonoids, lipids, etc., can be obtained from the isolation of silkworms (VTS).